Notary's Responsibility In Making A Deed Of Grant That Is Cancelled Due To Legal Defects - Sudaryanto, Muhammad Riyadi; Arifulloh, Achmad (Jurnal Konstatering, 2026)
This study analyzes the Village Treasury Land (TKD) dispute between the Sobokerto Village Government and the Indonesian Air Force (TNI-AU) in Ngemplak District, Boyolali Regency, which gave rise to dual claims over land that had been managed by the community for decades as a village asset but was later claimed as part of the strategic area of Adi Soemarmo Air Base. The dispute resulted in legal uncertainty regarding the land's status, overlapping ownership documents, reduced access for residents to cultivated land, and the weakening of the function of village assets as a supporter of Village Original Income. The study used a juridical-empirical method with a descriptive qualitative research type through a legislative and conceptual approach, with primary and secondary data obtained through in-depth interviews and literature studies, then analyzed descriptively-analystically. The results of the study indicate that the legal status of the disputed land is in a dualism of public legitimacy: the Village Government bases its claim on historical-factual control, recording of village assets, and the social function of TKD for the welfare of residents, while the TNI-AU positions it as a defense area controlled by the state for the sake of national security. This dualism is reinforced by the weak demarcation of boundaries and formal evidence of TKD in the past, thus triggering overlapping documents. The main obstacles include disorderly land registration administration, differences in ownership history that are not jointly verified, data asymmetry across agencies, the dominance of a legal-formal approach that ignores the social function of land, and unequal civil-military relations; within the framework of the Theory of Legal Certainty and Progressive Law Theory, these findings emphasize the need for integrated land administration arrangements, collaborative verification of ownership history, and resolution mechanisms that are not merely formalistic so that legal certainty and socio-economic protection of village communities can be restored.